Digital Marketing Strategy Development to Increase Sales for Fashion MSMEs (Case Study: Abang Jenggot Moslem Store) - Didit Hansari; Wulan Dayu; Hendra Utama (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the development of digital marketing strategies to increase sales at Abang Jenggot Moslem Store, a Muslim men's fashion business in Medan, and to identify factors causing low online sales conversion despite having social media accounts with a large number of followers. This research employed a descriptive qualitative approach with a case study method. Data were collected through semi-structured interviews with the business owner, a social media admin, and 10 customers. Non-participatory observation was conducted on the Instagram account (@abangjenggot_moslemstore), TikTok account, and Shopee account. Documentation included sales archives, social media insights, and screenshots of interactions. Data analysis used the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data display, and conclusion drawing. Observation of the @abangjenggot_moslemstore Instagram account during the January–February 2026 period revealed that average organic engagement remained relatively low, with likes ranging from 1 to 17 per post. However, an anomaly was found in posts involving influencers, which successfully garnered 530 likes and 66 comments. This finding indicates that influencer marketing strategies have significant potential to boost interaction, although their implementation remains sporadic and has not yet become part of a structured routine strategy. Furthermore, interviews with customers revealed that the majority learned about Abang Jenggot Moslem Store through direct interaction at the physical location or recommendations from friends, rather than through social media content. This confirms that the managed social media accounts have not been effective as customer acquisition channels, despite the Instagram account having a substantial follower base (12,900) and over 3,000 posts. This condition reinforces the gap between a strong quantitative digital presence and the business results achieved. This research is limited to a single case study of a fashion MSME in Medan; thus, the results cannot be generalized to the broader context of MSMEs or other industrial sectors. The researcher's limitations in this case study at Abang Jenggot Moslem Store pertain to the transaction data on the number of online sales occurring over a 7-year period. Information regarding the marketing strategies implemented was only sourced from interviews with the owner/leader, unaccompanied by well-documented written data from the business owner/leader. This research provides practical contributions in the form of structured digital marketing strategy recommendations for fashion MSMEs, particularly in addressing the gap between follower count and sales conversion. Theoretically, this study enriches the literature on the application of digital marketing in the Indonesian MSME sector.